Biogeochemical Dynamics Research in the Anthropocene - Slaveykova, Vera I. (Frontiers in Environmental Science, 2019)
The present paper provides a perspective on selected key issues driving inquiry in biogeochemical dynamics research of 21st century, which could contribute to filling of knowledge gaps towards development of the systems biogeochemistry approach. The specific focus is on understanding of the multiscale processes and effects involving elements and chemical compounds, their interactions with other environmental variables, as well as the development of integrative quantitative models and their validation. The special attention is paid on the necessity to decipher the biogeochemical dynamics of the novel entities and combinations of inorganic and/or organic chemicals in the environment, as well as their critical linkages and feedbacks with major nutrient cycles, the interplays with climate change and other anthropogenic stressors. Taking advantage of rapidly developing omics approaches and stable isotopes of non-traditional metals as well as the synergies arising from their integration in the biogeochemical modelling are discussed together with their potential to transform biogeochemical studies and push towards new frontiers in biogeochemical dynamics knowledge.